Effect of microplastics and arsenic on nutrients and microorganisms in rice rhizosphere soil - Youming Dong (Ecotoxicology and Environmental Safety, 2021)
The presence of microplastics and arsenic in soil can endanger crop growth; therefore, their effects on the properties of rhizosphere soil should be evaluated. Large (10–100 µm) and small (0.1–1 µm) polystyrene (PSMP) and polytetrafluorethylene (PTFE) particles were added to soil with different arsenic concentrations (1.4, 24.7, and 86.3 mg kg−1) to investigate the combined effect of microplastics and arsenic pollution on rice rhizosphere soil. After the addition of PSMP and PTFE, pH, arsenic (V) and arsenic (III) in the soil were observed to decrease. The interaction of arsenic with PSMP and PTFE resulted in this phenomenon, leading to a decrease of arsenic bioavailability in the soil. PSMP, PTFE, and arsenic reduced the abundance of Proteobacteria, increased the abundance of Chloroflexi and Acidobacteria, and inhibited soil urease, acid phosphatase, protease, dehydrogenase, and peroxidase activity via affecting the tertiary structure of the enzyme. PSMP, PTFE, and arsenic also reduced the available nitrogen and phosphorus content in the soil. Arsenic increased the soil organic matter content, whereas PSMP and PTFE reduced the organic matter content. Furthermore, microplastics inhibited the effects of arsenic on the microbial and chemical properties of the rhizosphere soil. This study revealed the effects of microplastic and arsenic pollution on rice rhizosphere microorganisms and nutrients, and elucidated the mechanism by which these pollutants retard crop growth in the designed growth medium.